Queer rebellion in the novels of Michelle Cliff : intersectionality and sexual modernity - Ilmonen, Kaisa (Cambridge Scholars Publishing, 2017)
This book explores Jamaican-American author Michelle Cliff's (1946-2016) literary rebellion against the colonial, gendered and racist norms of Western Modernity. It studies the sexualized circuits of the Atlantic world, drawing on the fields of literary criticism, feminist theories, queer studies and Caribbean studies. In order to do this, the book develops the theoretical paradigm of intersectionality. It also addresses the disturbing questions concerning the sexual politics of transatlantic modernity as represented in Cliff's novels. Cliff's rebellious poetics envisions the colonial Caribbea.